Factors Influencing the Operational Efficiency ofNong Chok Metropolitan Police Station - โพธิ์เกษม ภนิดา; สูติปัญญา พรเทพ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objectives of this study were 1) to study the factors affecting the performance of Nong Chok Metropolitan Police Station and 2) to study and compare the performance of Nong Chok Metropolitan Police Station. The sample group was 75 police officers. The research instrument was a questionnaire with a 95% reliability. The data analysis calculated statistics such as frequency, percentage, standard deviation, t-test, F-test, and pairwise differences using the Least Significant Difference method. The results of the research found that the factors affecting the performance of Nong Chok Metropolitan Police Station in general were structure, followed by strategy, management style, system, personnel, and ability, respectively. The performance of Nong Chok Metropolitan Police Station in general was work volume, followed by time and quality of work, respectively. The comparison of the performance of Nong Chok Metropolitan Police Station found that status, education level, and income had a significant effect on the performance of Nong Chok Metropolitan Police Station in terms of work quality, work volume, and time at a statistical level of .05